PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS SEKOLAH SMK NEGERI KABUPATEN BELALAWAN DI PEKANBARU - Sinaga, Wenny Juleha; Sembiring, Sabeth (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to prove that Participation in Budgeting and Reporting Systems has an effect on Performance Accountability of the Pelalawan District Vocational High School in Pekanbaru. The sample in this study was obtained by simple random sampling, with a total sample of 52 respondents. Data collection technique is by distributing questionnaires. The data analysis technique used is descriptive statistical analysis, data quality test, classical assumption, multiple linear regression and hypothesis testing using t test and f test with a significance level of 5% using SPSS 26. From the results of research using SPSS, it is known that the coefficient of determination (R Square) is 0.563. Participation in Budgeting and Reporting Systems together affects Performance Accountability by 56%. Based on the results of multiple linear regression analysis, it can be concluded that Participation in Budgeting and Reporting Systems has a positive and significant impact on the Accountability of Performance in the Pelalawan District Vocational School in Pekanbaru. The higher the Participation in Budgeting and Reporting Systems it will affect Performance Accountability. Keywords: Participation in Budgeting, Reporting System, Performance Accountability